The Special Safeguard Mechanism (SSM) and Tariffs: Price Behaviour with Imperfectly Competitive Market Intermediaries - Donald MacLaren (Center for Economic Studies and ifo Institute (CESifo), 2014)
The SSM is a proposal from the G-33 Group in the Doha Round negotiations in which developing countries would be allowed to use contingent tariffs to control import surges of food commodities and/or downward spikes in their border prices. The principal objective is to safeguard the livelihood security of farm households in these countries. A stochastic partial equilibrium model of a typical importing country situation is specified in which there are either imperfectly competitive, domestic intermediaries or a parastatal. Using Monte Carlo simulation, it is found that the objective of the SSM is unlikely to be met.
Keywords: F12; F13; Q17; 330